2018
DOI: 10.1186/s12939-018-0789-x
|View full text |Cite
|
Sign up to set email alerts
|

Do free caesarean section policies increase inequalities in Benin and Mali?

Abstract: BackgroundBenin and Mali introduced user fee exemption policies focused on caesarean sections (C-sections) in 2005 and 2009, respectively. These policies had a positive impact on access to C-sections and facility based deliveries among all women, but the impact on socioeconomic inequality is still highly uncertain. The objective of this study was to observe whether there was an increase or a decrease in urban/rural and socioeconomic inequalities in access to C-sections and facility based deliveries after the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 46 publications
(39 reference statements)
4
29
0
Order By: Relevance
“…Among included studies, national legislation or policy adoption promoting the access to and utilisation of SRH services spanned the period from 1996 to 2013, with a concentration of studies conducted between 2000 and 2009 (Supplemental Figure 4). Most studies analysed SRH service utilisation from one to eight years before and one to eight years after legislation/policy adoption (23,25,27,30,31,33,38,(42)(43)(44)(45)(46)(47)(48) and between 1 and 14 years after legislation/policy adoption (26,28,29,32,34,37,40,41,(49)(50)(51)(52)(53)(54). Two studies examined service utilisation two to four years before legislation/ policy adoption at time point 1 and the same year at time point 2 (24,39).…”
Section: Type Of Legislation and Srh Services Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Among included studies, national legislation or policy adoption promoting the access to and utilisation of SRH services spanned the period from 1996 to 2013, with a concentration of studies conducted between 2000 and 2009 (Supplemental Figure 4). Most studies analysed SRH service utilisation from one to eight years before and one to eight years after legislation/policy adoption (23,25,27,30,31,33,38,(42)(43)(44)(45)(46)(47)(48) and between 1 and 14 years after legislation/policy adoption (26,28,29,32,34,37,40,41,(49)(50)(51)(52)(53)(54). Two studies examined service utilisation two to four years before legislation/ policy adoption at time point 1 and the same year at time point 2 (24,39).…”
Section: Type Of Legislation and Srh Services Usedmentioning
confidence: 99%
“…Four other studies examined the effects of a reproductive health programme (35), performance-based financing (40), national health insurance (32), and exemption fees (32) or free health care (29) for pregnant women and lactating mothers on family planning and contraception. Five studies considered policy pertaining to caesarean sections (33,34,45,47,53). To a lesser extent, postnatal care (35,43,44,52) and PMTCT (29,39) were studied.…”
Section: Type Of Legislation and Srh Services Usedmentioning
confidence: 99%
“…A study found that there are differences in health, access to and quality of healthcare between rural and urban areas in the United States [1] [2] [3]. Several studies in Africa and the European Union also revealed the same thing [4][5] [6] [7]. Thus it can be concluded that the disparity in health services between urban and rural areas is still a global problem.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the context of maternal health, Ghana introduced free facility deliveries in 2003 (Bosu et al, 2007), Senegal in 2005 (Witter et al, 2010) and Burkina Faso subsidised user fees in 2007 (Ridde et al, 2015). Mali removed user fees for only caesarean deliveries in 2005, followed by Benin andMorocco in 2009 (Dossou et al, 2018;Ravit et al, 2018;Witter et al, 2016). Evidence from these schemes show that demand-side interventions that reduce barriers to access by reducing or eliminating user fees at health facilities make healthcare more equitable as poor households are now more likely to access healthcare (Peters et al, 2008;Ridde & Morestin, 2011); albeit the poorest are still often the least likely to utilise facility-based care (Ridde et al, 2015).…”
Section: Introductionmentioning
confidence: 99%